Rhododendron hybrid "Frosthexe" at the Arctic and Alpine Botanic Garden in Tromsø, Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
This rhododendron was one of many in bloom at the Arctic and Alpine Botanic Garden (latitude 69.6769° N) in Tromsø, Norway in early June, 2024. The text reads "Lyngfamillen. 2014-541-G. Rhododendron-hybriden "Frosthexe". Hage-hybriden R. anthopogon x lapponicum. Gave fra Ole P. Olsen". This plant had a low profile and small, vibrant pink purple flowers. ...